2009
DOI: 10.1080/15325000903055271
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of a Permanent Magnet Machine with Two Contra-rotating Rotors

Abstract: Electrical machines with contra-rotating rotors find applications in directdrive energy conversion systems and in ship propulsion systems that employ hydraulic machinery with two contra-rotating stages. In this article, the operating characteristics of permanent magnet machines with two contra-rotating rotors moving on opposite sides of a common stator core are studied via two-dimensional finite element analysis. Particular attention is devoted to the special flux distortion patterns that arise in contra-rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Where, m 1 is number of phases of each stator, m is number of phases of the machine, K p is termed the electrical power waveform factor, K e is the EMF factor which incorporates the winding distribution factor K w and the per unit portion of the total air gap area spanned by the salient poles of the machine (if any), K i is the current waveform factor, A is the electrical loading, ɳ is machine efficiency, N ph is the number of turn per phase, B g is the flux density in the air gap, f is the converter frequency, p is the machine pole pairs, λ is the diameter ratio for AFPG defined as D i /D o , D o is the diameter of the machine outer surface, D i is the diameter of the machine inner surface [1,[3][4][5][6].…”
Section: Sizing Equation Of Afpgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where, m 1 is number of phases of each stator, m is number of phases of the machine, K p is termed the electrical power waveform factor, K e is the EMF factor which incorporates the winding distribution factor K w and the per unit portion of the total air gap area spanned by the salient poles of the machine (if any), K i is the current waveform factor, A is the electrical loading, ɳ is machine efficiency, N ph is the number of turn per phase, B g is the flux density in the air gap, f is the converter frequency, p is the machine pole pairs, λ is the diameter ratio for AFPG defined as D i /D o , D o is the diameter of the machine outer surface, D i is the diameter of the machine inner surface [1,[3][4][5][6].…”
Section: Sizing Equation Of Afpgsmentioning
confidence: 99%
“…Selecting double-sided AFPGs with high power density is an important parameter. So, comparison of power density between different topologies of double-sided AFPGs seems to be necessary [1,3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In conventional machines, the air gap flux density has normally radial direction; in AFPGs, the air gap flux density presents mainly axial direction. In general, AFPGs exhibit an axial length much smaller than the length of a conventional generator of the same rating [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this paper presents an investigation into the characteristics of the back-EMF and torque production of the axial-flux PMSM with contra-rotating rotors under unbalanced load. Related research can only be found in [15]- [16], which investigated a radial-flux PMSM with contra-rotating rotors and analyzed the mutual effects of the two rotors through the common stator based on 2-D FEA (finite element analysis). The results suggested that the peak value of the back-EMF in the stator winding is related to the relative position of the two rotors.…”
mentioning
confidence: 99%